2016
DOI: 10.1088/0953-8984/28/9/094005
|View full text |Cite
|
Sign up to set email alerts
|

Pentacene on Au(1 1 1), Ag(1 1 1) and Cu(1 1 1): From physisorption to chemisorption

Abstract: We measured the electronic and the molecular surface structure of pentacene deposited on the (1 1 1)-surfaces of coinage metals by means of ultraviolet photoelectron spectroscopy (UPS) and low-energy electron diffraction (LEED). Pentacene is almost flat-lying in monolayers on all three substrates and highly ordered on Au(1 1 1) and on Cu(1 1 1). On Ag(1 1 1), however, weak chemisorption leads to almost disordered monolayers, both, at room temperature and at 78 K. On Cu(1 1 1) pentacene is strongly chemisorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(104 citation statements)
references
References 79 publications
10
93
1
Order By: Relevance
“…Both PBE and PBE+vdW surf , however, predict flat conformation for pentacene/Ag(111), as can be seen in Fig. 6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 88%
“…Both PBE and PBE+vdW surf , however, predict flat conformation for pentacene/Ag(111), as can be seen in Fig. 6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 88%
“…A monochromatized Al Kα source (1486.7 eV) and a monochromatized HeI (21.22 eV) were used as XPS and UPS excitation source, respectively. Detailed sketch of the measurement geometry was shown in our previous work . Kinetic energy scale in the plot of the secondary electron region of UPS was corrected by a −3 V bias voltage and the analyzer work function.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the conformation and orientation of the organic semiconductor molecules on the metal and amount of chemical bonding can vary based on the surface energetics and chemistry, a process that also results in shifts in φ B . When molecules are physisorbed, they couple weakly to the metal surface and the alignment of energy levels can approach the Schottky–Mott limit, where φ B is controlled by the metal work function and the semiconductor HOMO/LUMO levels . For strong molecule–metal interactions, such as the case of chemisorbed molecules, charge transfer from the metal to the semiconductor molecules leads to the formation of large surface dipoles, making the band diagram of the isolated material surfaces irrelevant .…”
Section: Charge Injection Through a Metal–semiconductor Interfacementioning
confidence: 99%
“…When molecules are physisorbed, they couple weakly to the metal surface and the alignment of energy levels can approach the Schottky–Mott limit, where φ B is controlled by the metal work function and the semiconductor HOMO/LUMO levels . For strong molecule–metal interactions, such as the case of chemisorbed molecules, charge transfer from the metal to the semiconductor molecules leads to the formation of large surface dipoles, making the band diagram of the isolated material surfaces irrelevant . The strength of the coupling between the organic semiconductor and the electrode can be tuned, to a certain extent, by processing.…”
Section: Charge Injection Through a Metal–semiconductor Interfacementioning
confidence: 99%
See 1 more Smart Citation